2017
DOI: 10.4236/wjet.2017.52022
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Analysis Web Opening of Steel Beams

Abstract: According to the purpose of the opening and the structural designer, the shape of the web opening is decided. It is too easy to choose the shape of openings from regular shape whether it is circular or rectangular shape. The presence of openings in the web of steel beams decreases stiffness of the beam and introducing a larger deflection than in the steel web opening with solid opening. A steel beam with web opening is analyzed in this paper. ABAQUS software is using for analyzing nonlinear static and dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Hence, study of web opening is needed to be done in order to produce steel section with least material but results in highest efficiency without compromising the safety factor consideration. However, based on the static and dynamic analysis, the higher values of stresses are observed near the opening (El-Dehemy, 2017). Besides that, the best location of web opening is middle two-third of the span (Morkhade and Gupta, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, study of web opening is needed to be done in order to produce steel section with least material but results in highest efficiency without compromising the safety factor consideration. However, based on the static and dynamic analysis, the higher values of stresses are observed near the opening (El-Dehemy, 2017). Besides that, the best location of web opening is middle two-third of the span (Morkhade and Gupta, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the corners of rectangular openings are prone to high-stress concentrations, making them more critical than circular openings. The impact load response of steel structures and their relationship with the initial shape has only been examined in a few studies [9,11,48]. Based on their research, the reasons for failure differed significantly depending on the shape of the openings.…”
Section: Opening Shapementioning
confidence: 99%
“…It was found that the shape of the web opening has a minor effect on the natural frequency. El-Dehemy [13] analyzed the stress and deflection patterns of steel beams with web openings (SBWOs). The results showed that the deflection value of the steel beam increased as the number of openings increased.…”
Section: Introductionmentioning
confidence: 99%